2010
DOI: 10.1213/ane.0b013e3181f9c035
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam Decreases Action Potential Firing of Neocortical Neurons via Two Distinct Mechanisms

Abstract: Diazepam induced a biphasic attenuation of spontaneous action potential firing of neocortical neurons. Low to moderate concentrations caused a monotonic, mild depression that is mediated via the classical binding site as it is antagonized by flumazenil. However, the effects of diazepam observed at high concentrations were not affected by flumazenil. Hence, these findings support the concept of at least 2 different binding sites for benzodiazepines on γ-aminobutyric acid type A receptors. Furthermore, our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
9
29
0
Order By: Relevance
“…This is in close agreement with results obtained from previous studies with diazepam 11, 14 . The most convincing hypothesis to explain this biphasic depression is the existence of at least two benzodiazepine binding sites, as proposed by Walters et al ., leading to two separate mechanisms of benzodiazepine action 14 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in close agreement with results obtained from previous studies with diazepam 11, 14 . The most convincing hypothesis to explain this biphasic depression is the existence of at least two benzodiazepine binding sites, as proposed by Walters et al ., leading to two separate mechanisms of benzodiazepine action 14 .…”
Section: Discussionsupporting
confidence: 93%
“…There are, however, several possibilities to explain this finding: First, a saturation at the classical benzodiazepine site 11 and second, a novel binding site for benzodiazepines at the GABA A receptor, preventing further depression, as suggested in a previous study by Baur et al . 20 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In accordance with these findings in rodents, functional magnetic resonance imaging studies showed that sedative drugs reduce blood flow predominantly in neocortical circuits of human subjects (Heinke and Koelsch, 2005). On the cellular level, benzodiazepines significantly depress action potential activity of neocortical neurons (Drexler et al, 2010), supporting the idea that this action is causally linked to sedation. Neocortical neurons express a great diversity of GABA A receptor-subtypes (Fritschy and Brünig, 2003).…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, anesthetic agents depress action potential firing and oscillatory network activity in neocortical brain slices (Lukatch et al 2005) and organotypic cultures (Antkowiak and Helfrich-Forster 1998). Similar effects were seen with benzodiazepines (Drexler et al 2010) and barbiturates (Lukatch and MacIver 1996) which are used clinically to induce sedation. To date, brain slice assays have not been utilized in the assessment of potential sedative effects, and this is unlikely to be used as a routine screen in preclinical safety assessment.…”
Section: In Vitro Sleep And/or Sedation Assessmentmentioning
confidence: 78%